ASSESSING THE IMPACT OF PARENTAL ATTITUDES ON THE CHILD'S PSYCHOLOGICAL WELLBEINGWHEN CONDUCTING EXPERT PSYCHOLOGICAL EVALUATIONS IN FAMILY DISPUTES - E. Polkunova (Теория и практика судебной экспертизы, 2015)
The paper addresses the issues of assessing the impact of parents' individualpsychological characteristics on the child's mental development, as an element offorensic psychological evaluations in family disputes. These issues mostly arisedue to the lack of a uniform science-based methodological approach andunderdevelopment of currently used approaches. The author reviews theoreticalapproaches to investigating the impact of parental attitudes on the child's mentalcondition, including the development of affective spectrum disorders, and proposesan original experimental methodology for the study of parental attitudes.